Evaluation of Liquid Organic Fertilizers for Containerized Production under Controlled Environment - Milon Chowdhury; Oliver Watson; Uttara C. Samarakoon; James E. Altland; Joanna Moine (HortScience)
Organic production is becoming increasingly popular among producers in controlled environment agriculture. However, selecting a suitable fertilizer for organic production can be complicated, as commercially available organic fertilizers have widely different nutrient compositions. The goal of this study was to evaluate the effectiveness of several liquid organic fertilizers and compare their performance with a synthetic fertilizer for growing lettuce and dwarf tomato in containerized production systems under a controlled environment. Two consecutive experiments were conducted. In Expt. 1, three commercial liquid organic fertilizers [earthworm castings (F1), sugarcane molasses (F2), and fish emulsion (F3)] were evaluated under two different containerized systems [Dutch bucket (DB) and regular plastic container (RPC)]. The best-performing fertilizers (F1, F2) were then compared with synthetic fertilizer (F4) in Expt. 2. In Expt. 1, lettuce was harvested 14 and 28 days after transplanting to assess shoot growth. In Expt. 2, dwarf tomato was also considered along with the lettuce, which were harvested 60 and 30 days after transplanting, respectively. Besides evaluating the regular growth parameters in both experiments, lettuce leaf tissue and leachate analyses were performed in Expt. 2. In Expt. 1, the F1 fertilizer outperformed F2 and F3, resulting in a 28% and 32% higher fresh weight in the DB system, and a 57% and 41% higher fresh weight in the RPC system, respectively. In addition, F1 led to improvements in the RPC system compared with the DB system, with increases of 28% in fresh weight, 20% in dry weight, 48% in leaf area, 26% in shoot width, 126% in root fresh weight, and 47% in root length. In Expt. 2, results showed that F1 performed similar to or better than F4 for growing lettuce and dwarf tomatoes in container hydroponic systems. Leaf tissue and leachate analyses also showed similar results. The findings of this study indicate that synthetic fertilizer could be replaced by some liquid organic fertilizers, and a single organic fertilizer could be used instead of several for organic leafy green production. Fruit crops such as tomato may require more than one organic fertilizer to provide the correct ratio of all nutrients.